The optimal monetary and fiscal policy mix in a financially heterogeneous monetary union - Jakob Palek (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
Recent work on financial frictions in New Keynesian models suggest that there is a sizable spread between the risk-less interest rate and the borrowing rate. We analyze the optimal policy mix of monetary and fiscal authorities in a currency union with a country-specific credit spread by introducing a cost channel differential. The cost channel decreases the efficiency of monetary policy and increases the need for fiscal stabilization. We show that the importance of fiscal policy in stabilizing shocks increases, when there is a gap in the inflation differential due to a relative shock, an idiosyncratic shock or a credit spread differential. The welfare losses will be increasing (decreasing) in the size of the cost channel, if the nominal interest rate is a demand- (supply-) side instrument.
Keywords: E31; E52; E62; E63; 330; cost channel; financial frictions; credit spreads; optimal monetary policy; fiscal policy; monetary union